Comparison of Continuous Versus Simple Interrupted Polypropylene Suture Closure of Midline Emergency Laparotomy Wound in Terms of Wound Outcome in Adult Patients Presenting with Acute Abdomen: Continuous Vs Interrupted Polypropylene Suture Closure of Laparotomy Wound - Nasir, Mubeen; Siddique, Muhammad; Zaeem, Ahmad; Raza, Ali; Rizwan, Muhammad; Abbas, Mudasir (Pakistan Journal of Health Sciences, 2025)
The best method and material for sutures to use while closing wounds are still unknown. This study aimed the results of this trial to determine which method works best and should be recommended as hospital policy. Objectives: To compare outcomes of simple interrupted versus continuous closure techniques using no.1 polypropylene sutures for emergency midline laparotomy wounds regarding frequency of wound dehiscence. Methods: This quasi-experimental study was conducted after obtaining approval from the College of Physicians and Surgeons Pakistan over six months from June 2024 to December 2024. 104 emergency midline laparotomy patients were recruited from the Surgical Department of Sir Ganga Ram Hospital, Lahore. Patients were divided into 2 groups A, continuous suture closure and Group B, simple interrupted suture closure. Postoperatively patients were observed for wound dehiscence. Data were analyzed using SPPS version 26.0. The occurrence of dehiscence was compared among groups using the chi-square test. Results: Wound dehiscence was found to be higher in Group A as compared to Group B. Group A: 21.1% vs. Group B: 11.5%, and p-value=0.185. Gender and Body mass index had no significant association with wound dehiscence in study groups. However, among the younger age group patients’ frequency of wound dehiscence was significantly higher while among the elderly age group, no significant difference was obtained. Conclusions: It was concluded that results of this study showed no significant difference for wound dehiscence for simple interrupted suture compared with versus continuous closure techniques using polypropylene suture for patients who underwent emergency midline laparotomy.